Pengembangan Budaya Religius Dalam Membentuk Karakter Siswa di Di SMK Hidayatus Sholihin Turus Gurah Kediri - Wasito; Makhfud (Universitas Islam Tribakti Lirboyo Kediri, 2020)
Religious culture in schools is an activity to manifest the values of religious teachings as a tradition of behaviour that is followed by all school members which is carried out consistently. However, currently, there are many phenomena regarding bad morals among students of SMK Hidayatus Sholihin Gurah, Kediri Regency. The method in this research is discretive qualitative, the data collection method uses observation, interview and documentation. Then analyzed using descriptive / exposure data from the results of observation interviews and documentation. As a result, the development of religious culture at SMK Hidayatus Sholihin is able to shape the character of students according to the vision, mission and goals of the institution. The main supporting factor is the qualification of Islamic Religious Education (PAI) teachers who are competent in their field.